Wild jujube polysaccharides protect against experimental inflammatory bowel disease by enabling enhanced intestinal barrier function. Issue 8 (5th August 2015) - Yue, Yuan; Wu, Shuangchan; Li, Zhike; Li, Jian; Li, Xiaofei; Xiang, Jin; Ding, Hong
<x xml:space="preserve">Abstract</x> Dietary polysaccharides provide various beneficial effects for our health.